Pengaruh Pembiayaan Bagi Hasil, NPF Dan FDR Terhadap Profitabilitas (ROA) - Nur Rantika Octavia; Wirman Munaraja (FEB Universitas Sultan Ageng Tirtayasa, 2022)
ABSTRAK. The purpose of this study is to find out how big the Effect of Profit Sharing Financing, Non Performing Financing (NPF) and Financing to Deposit Ratio (FDR) on Profitability (ROA) in Islamic Commercial Banks for the 2018-2020 period. The method used is descriptive verification method with a quantitative approach assisted by the SPSS program, the data used in this study is secondary data. This study uses a population at Islamic Commercial Banks for the period 2018-2020 using purposive sampling technique. Based on the results of the t-test partially Profit Sharing Financing has a positive and significant effect on Profitability (ROA), while Non Performing Finance (NPF) and Financing to Deposit Ratio (FDR) have a negative and insignificant effect on Profitability (ROA). Simultaneously Profit Sharing Financing, Non Performing Finance (NPF), and Financing to Deposit Ratio (FDR) have a positive and significant effect on Profitability (ROA).